2023
DOI: 10.2147/prbm.s395035
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Pandemic (COVID-19) Mental Health of International Students: Data from a Longitudinal Study

Abstract: International students are highly vulnerable to the risk of mental health worsening before and during the pandemic . This study investigated international students' mental health pre-and post-pandemic (COVID-19). Methods: It is a longitudinal study, and data were collected online, pre-pandemic (N = 470) and during the pandemic (N = 420). Using a random sampling technique, a self-administered questionnaire was used to measure mental health, including depression and anxiety. Results: Findings show that internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 92 publications
0
4
1
Order By: Relevance
“…Gender-wise, first-year female students reported more symptoms of anxiety than males, however, by the second year of studies this difference had disappeared. Those findings contradict the results of other studies which showed that females were more mentally vulnerable than males during the COVID-19 outbreak and had a higher prevalence of anxiety [ 33 – 36 ]. However, a retrospective survey by Hendriksen et al [ 37 ] similar to our study revealed that the difference in gender was observed only during the first lockdown at the beginning of the pandemic (from March to May 2020), and it ceased to be significant later in the period of second lockdown from November 2020 to May 2020.…”
Section: Discussioncontrasting
confidence: 99%
“…Gender-wise, first-year female students reported more symptoms of anxiety than males, however, by the second year of studies this difference had disappeared. Those findings contradict the results of other studies which showed that females were more mentally vulnerable than males during the COVID-19 outbreak and had a higher prevalence of anxiety [ 33 – 36 ]. However, a retrospective survey by Hendriksen et al [ 37 ] similar to our study revealed that the difference in gender was observed only during the first lockdown at the beginning of the pandemic (from March to May 2020), and it ceased to be significant later in the period of second lockdown from November 2020 to May 2020.…”
Section: Discussioncontrasting
confidence: 99%
“…Among international students, mean scores of depressive symptoms reflected clinically relevant depressive symptoms for all timepoints, whereas domestic students presented a mean score indicating clinically relevant depressive symptoms only in 2021. Our results can be compared to a longitudinal study in China that found significantly more depressive symptoms among international students in the so-called post-pandemic (October to December 2021) assessment compared to the pre-pandemic (December 2019 to April 2020) timepoint [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demographic data indicated that international students were older and a higher proportion of them exercised habitually. It has been reported that being younger [18,26,27] and not having exercise habits [28] were factors associated with worsened mental health during the COVID-19 pandemic. Thus, these attributes of international students appeared to serve as protective factors against worsened mental health during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…That study did not conduct a comparison with domestic students, leaving uncertainty regarding whether the effects were specific to international students or applicable to university students in general. In a study by Jamshaid et al, indicators of depression and anxiety worsened among Chinese international students after the pandemic, with youth and female gender identified as risk factors [18]. The baseline survey period labeled as "pre-pandemic" in this study spanned from December 2019 to April 2020, potentially including periods not strictly considered pre-pandemic, such as between the onset of the outbreak in China (December 2019) and the WHO's recognition of the pandemic (11 March 2020).…”
Section: Introductionmentioning
confidence: 99%